2014
DOI: 10.3389/fimmu.2014.00334
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Toll-Like Receptor 4 in Colorectal Cancer

Abstract: Toll-like receptor (TLR) signaling has been implicated in the inflammatory responses in intestinal epithelial cells (IECs). Such inflammatory signals mediate complex interactions between commensal bacteria and TLRs and are required for IEC proliferation, immune response, repair, and homeostasis. The upregulation of certain TLRs in colorectal cancer (CRC) tissues suggests that TLRs may play an essential role in the prognosis of chronic and inflammatory diseases that ultimately culminate in CRC. Here, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 126 publications
3
65
1
Order By: Relevance
“…Our study further substantiates and extends our knowledge concerning the role of TLR4 in previous studies involving both intestinal and breast tumors (Santaolalla et al, ; Yang et al, ; Yesudhas et al, ). TLRs defend against invading microorganisms by recognizing various motifs of microbial origin called pathogen‐associated molecular patterns (PAMPs) (Janeway and Medzhitov, ; Akira et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Our study further substantiates and extends our knowledge concerning the role of TLR4 in previous studies involving both intestinal and breast tumors (Santaolalla et al, ; Yang et al, ; Yesudhas et al, ). TLRs defend against invading microorganisms by recognizing various motifs of microbial origin called pathogen‐associated molecular patterns (PAMPs) (Janeway and Medzhitov, ; Akira et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, KO mice exhibited higher levels of other Gram negative bacteria that are able to stimulate TLR4 and increase its expression, such as Clostridium (Scarpa et al, 2011), B. vulgates (Haller et al, 2004), Acinetobacter (Erridge et al, 2007), or Pseudomonadaceae (Korneev et al, 2015). Today it is widely accepted that in normal intestinal epithelial cells, TLR4 is marginally expressed but under pathological conditions such as IBD and CRC an overexpression of this receptor occurs (Yesudhas et al, 2014). However, it has not been well established whether this TLR4 elevation occurs prior to IBD breakout or is a consequence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In normal gut, intestinal epithelial cells maintain a beneficial link with the microorganisms in the intestinal flora through toll-like receptors (TLRs), which mediate signaling to maintain epithelial cell integrity and tight junctions (Yesudhas et al, 2014). Stimulation from commensal bacteria is finite and should not trigger an excessive inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herszenyi et al (2014) proved that proteolytic enzymes play an important role in CRC metastasis. Yesudhas et al (2014) reported that TLR-4 was a critical target in CRC metastasis. In this study, we focused on exploring the potential cause of CRC metastasis and on screening molecular targets by the analysis of gene and miRNA expression profiles from microarray data.…”
Section: Introductionmentioning
confidence: 99%